Environment Monuments of Samarkand (Journal of Architectural Design, 2022)
In the article Self-developed historical housing construction is characterized by a wealth of expressive means of "architecture without architects", as well as the forms and construction that we inherit from generation to generation by artisans. 'that we may meet. the study of this architecture is reported to be the richest source of inspiration in the search for new modern architectural forms and methods.